Perception of Students on the Implementation of Indonesian Language Learning Model Based on Environment and Disaster Mitigation - Noprina, Winda; Jendriadi, Jendriadi; Putri, Solah Amelia (Postgraduate School, Universitas Negeri Padang, 2024)
Indonesia is a disaster-prone region. Data from the National Disaster Management Agency (BNPB) shows that the number of disasters in Indonesia has continued to increase up to 2021. Therefore, comprehensive risk management of disaster threats is urgently needed to reduce losses due to disasters. One way to achieve this is by implementing an environment-based and disaster mitigation learning model in Indonesian language education. This simple study aims to examine students' perceptions of the implementation of an environment-based and disaster mitigation learning model in Indonesian language education. This research is quantitative using a descriptive method. The data collection instrument was a questionnaire distributed to 47 students. About 74% of respondents had experienced a disaster and indicated low disaster preparedness when it occurred. The percentage of positive perceptions towards environment-based and disaster mitigation language learning was higher among students who had experienced disasters, at 88.5%. Although this is only a 3.5% difference from the positive perceptions of the 26% of students who had not experienced natural disasters, it shows that those who have experienced disasters and felt the direct impact of natural disasters consider the implementation of an environment-based and disaster mitigation Indonesian language learning model to be more important and necessary.